2022
DOI: 10.1021/acs.inorgchem.2c02421
|View full text |Cite
|
Sign up to set email alerts
|

3D/2D Heterojunction Fabricated from RuS2 Nanospheres Encapsulated in Polymeric Carbon Nitride Nanosheets for Selective Photocatalytic CO2 Reduction to CO

Abstract: Micro/nanostructure control of heterostructures is still a challenge for achieving high efficiency and selectivity of photocatalytic CO 2 conversion. In this work, a new three-dimensiona/two-dimensional (3D/2D) heterostructure is fabricated by encapsulating RuS 2 nanospheres in the interlayer of mesoporous polymeric carbon nitride (PCN) nanosheets based on an in situ growth and polymerization strategy. The unique microstructure of the obtained 3D/2D RuS 2 / PCN heterojunction can effectively improve the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…50,51 The discovery of Ru-S bonds further proves the successful preparation of RuS 2 @CN-2. 41 To further study the optical properties of CN and RuS 2 @CN-2, ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) was investigated. As compared with CN, the RuS 2 @CN-2 showed a red-shift in the visible light absorption range, indicating that RuS 2 @CN-2 has stronger light capture capability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 The discovery of Ru-S bonds further proves the successful preparation of RuS 2 @CN-2. 41 To further study the optical properties of CN and RuS 2 @CN-2, ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) was investigated. As compared with CN, the RuS 2 @CN-2 showed a red-shift in the visible light absorption range, indicating that RuS 2 @CN-2 has stronger light capture capability.…”
Section: Resultsmentioning
confidence: 99%
“…37 In addition to the above metal sulfides, RuS 2 is a semiconductor with a narrow band gap, high conductivity, and hydrogen adsorption free energy similar to Pt. 38–41 Furthermore, RuS 2 has been reported to form photocatalysts with TiO 2 , SiO 2 42 and other materials. 43 For instance, Maheu et al compounded RuS 2 and TiO 2 to obtain RuS 2 /TiO 2 and its photocatalytic activity gradually enhanced with increasing RuS 2 content.…”
Section: Introductionmentioning
confidence: 99%
“…S6†). 37–40 In addition to the photoelectrochemical characterization, we also analyzed the crystal face index of UCu1 and UCu2 and found that the exposed crystal surfaces in UCu1 are mainly (110) and (1̄10), while the exposed crystal surfaces in UCu2 are mainly (100) (Fig. S7†).…”
Section: Resultsmentioning
confidence: 99%
“…After the photocatalytic CO 2 reduction reaction, three transmittance peaks of intermediate products are detected on the sample Cu(2)–SnO 2 , including adsorbed/activated CO 2 * (1200–1300 cm −1 ), formate *COOH (1400–1500 cm −1 ), and bidentate bicarbonate b-HCO 3 − (1600–1650 cm −1 ). 23,35,36 The obvious transmittance peaks suggest that the adsorbed sample Cu(2)–SnO 2 can be effectively activated, and the appearance of the *COOH peak suggests that CO 2 reduction follows a *COOH pathway, which also explains the reason of the high selectivity of CO.…”
Section: Resultsmentioning
confidence: 99%